New boarding policies to improve the passenger experience in cable car transport systems. (5th April 2023) - Oberegger, Bernhard; Rabta, Boualem; Wankmüller, Christian; Reiner, Gerald
Current boarding approaches in cable car transport systems allow passengers to board freely whenever seats are available. During rush hours, cabins are usually loaded fully at the first station where the queue is fluid while passengers in subsequent stations have to wait long until boarding even when queues are short. This maximises throughput, but passengers at subsequent stations might feel unfairly treated. To improve passenger experience, we propose boarding policies to (re)balance the capacity at all stations. We develop a discrete event simulation (DES) model based on empirical data to analyse several boarding policies and to determine the best configuration that ensures 'fairness' instead of reducing only waiting times. Results show that using boarding policies reduces waiting times at subsequent stations to the detriment of passengers at the first station. However, this approach generates a fairer waiting time situation, indicating a better experience and less stress for cable car passengers.